Early initiation of continuous renal replacement therapy improves survival of elderly patients with acute kidney injury: a multicenter prospective cohort study. Issue 1 (December 2016) - Park, Jae; An, Jung; Jhee, Jong; Kim, Dong; Oh, Hyung; Kim, Sejoong; Joo, Kwon; Oh, Yun; Lim, Chun-Soo; Kang, Shin-Wook; Kim, Yon; Park, Jung; et al.
Abstract Background Continuous renal replacement therapy (CRRT) is essential in the management of critically ill patients with acute kidney injury (AKI). However, the optimal timing for initiating CRRT remains controversial, especially in elderly patients. Therefore, we investigated the outcomes of early CRRT initiation in elderly patients with AKI. Methods A total of 607 patients ≥65 years of age who started CRRT due to AKI between August 2009 and December 2013 were prospectively enrolled. They were divided into two groups based on the median 6-hour urine output immediately before CRRT initiation. Propensity score matching was used to compare the overall survival rate, CRRT duration, and hospitalization duration. Results The median age of both groups was 73.0 years, and 60 % of the patients were male. The most common cause of AKI was sepsis. In the early CRRT group, the mean arterial pressure was higher, but the prothrombin time and total bilirubin, aspartate aminotransferase, and alanine aminotransferase levels were lower. The overall cumulative survival rate was higher in the early CRRT group (log-rankP  < 0.01). Late CRRT initiation was associated with a higher mortality rate than early initiation after adjusting for age, sex, the Charlson comorbidity index, systolic arterial pressure, prothrombin time, the total bilirubin, aspartate aminotransferase, and alanine aminotransferase levels, cumulative fluid balance and diuretic use (hazard ratio, 1.35; 95 % confidence interval 1.06, 1.71, P  = 0.02). Following propensity score matching, patient survival was significantly better in the early CRRT group than in the late CRRT group (P  < 0.01). The total duration of hospitalization from the start of CRRT was shorter among the survivors when CRRT was started earlier (26.7 versus 39.1 days, P  = 0.04). Conclusion A better prognosis can be expected if CRRT is applied early in the course of AKI in critically ill, elderly patients.